Profile Multiple Intelligence Siswa SMA Negeri 5 Kerinci: Linguistic, Interpersonal, Intrapersonal - Iis Sholihat; Hengki Yandri; Dosi Juliawati (Indonesian Journal of Counseling and Development, 2021)
Students' ignorance of the potential they have, especially the intelligence they have, is an obstacle for students to be able to improve their achievements in school. For that, it needs to be revealed multiple intelligence profiles, especially linguistic, interpersonal, and intrapersonal intelligence of students. This research is a type of quantitative research with a descriptive approach. The population in this study was a student of State Junior High School 5 Sungai Penuh that amounted to 145 people and the study sample was taken with the formula Slovin with random sampling cluster sampling technique so that the number of samples in this study amounted to 107 people. This research instrument uses the Multiple Intelligence Scale that researchers develop themselves, and then the data that has been collected is tabulated and analyzed with descriptive statistics to calculate respondents' scores using ideal scores. The results of this study revealed that students' multiple intelligence profiles related to linguistic intelligence were in the medium category, then the student's interpersonal intelligence was in a low category, and the student's intrapersonal intelligence was in the medium category